Patterns of Single Nucleotide Polymorphism and Drought Tolerance in common bean (Phaseolus Vulgaris L.) (2011)
One of the main questions in genetics is the link between traits and genes. The differential selection pressures that have acted in genes, particularly those involved in stress response and the domestication syndrome, have left unique genetic signatures. Therefore, the scientific work to detect marker-trait associations is comparable to the search of those signatures. However, the recognition of such patterns requires a neutral background which tells us how genes look like in the absence of the pressure. Although coalescence theory has proven to be powerful to deal with this task, a multilocus survey is most adequate in species with a complex evolutionary history, for which an accurate coalescent simulation is unavailable. In particular, we followed this approximation to evaluate candidate genes for drought tolerance in common bean, a legume with two independent domestication processes in two partially isolated ancestral wild genepools. We present below a survey of the multilocus background based on EST-derived SNPs (section 1). After that, we screen two transcription factors (Dreb2A and Dreb2B) of the ABA-independent drought response pathway (section 2). We asked whether the variation at those genes diverges in relation with the background survey. This work is a prerequisite for finding the most efficient alleles for the more relevant genes, for the analysis of linkage disequilibrium along selected genes in comparison with neutral markers, for uncovering some of the genepool structure and selection history of the species, and for identifying orthologous genes based on phylogenetic and genealogical relationships between different crop species. All of these results can improve the association and comparative mapping for drought tolerance traits and establish a methodological pipeline for assessing diversity for any other orthologous gene. Ultimately, these initiatives will close the gap between structural polymorphism of these genes and their functional diversity.